KAJIAN IMPLEMENTASI KEBIJAKAN PEMBATASAN KEGIATAN MASYARAKAT (PKM) DALAM PENANGANAN PANDEMI COVID-19 DI KOTA SEMARANG TAHUN 2020 - Didik Try Putra; Muhammad Nuh (SPEKTRUM, 2021)
The Community Activity Restriction Policy (PKM) in Semarang City is a policy issued by the Semarang City government in accelerating the handling of the Covid-19 pandemic in Semarang City. The city of Semarang as the capital of Central Java Province is the area with the highest number of positive cases of Covid-19. The implementer of the Community Activity Restriction (PKM) policy is the Semarang City Covid-19 Task Force. The restrictions on community activities include 4 restrictions, namely the termination of the implementation of activities in schools and/or educational institutions, restrictions on activities in the workplace, restrictions on religious activities, and restrictions in public places. This study aims to describe the implementation process of the Community Activity Restriction Policy (PKM) carried out by the Semarang City Government and to describe the supporting and inhibiting factors of policy implementation. This research is a descriptive qualitative research. The data was collected by observation, document study, interview and online. Data analysis techniques include data reduction, compilation of data and conclusions. Test the validity of the data using triangulation of sources and techniques. The results of this study are the implementation of the Community Activity Restriction (PKM) policy in the city of Semarang showing the implementation of PKM through Perwal, PKM is communicated from the Health Service and the Covid-19 Task Force, facility resources have supported such as hospitals, isolation places, medical, health protocol facilities , psychologists and food assistance, the disposition of the Semarang City government through the Covid-19 Task Force and the Semarang City Health Service have shown their commitment to implementing the Community Activity Restriction (PKM) policy is good but the changes achieved have not been maximized, the bureaucratic structure and SOPs are clear stated in the Decree of the Mayor of Semarang Number 180/278 Year. Supporting factors: communication, support, resources, and bureaucratic structure. Inhibiting factors: the disposition of the government that is committed but the people who tend to violate the rules of Restricting Community Activities (PKM). Keywords: Implementation, Policy, Restriction of Community Activities (PKM), Semarang City. Abstrak Kebijakan Pembatasan Kegiatan Masyarakat (PKM) di Kota Semarang merupakan kebijakan yang di keluarkan pemerintah Kota Semarang dalam percepatan penangan pandemi Covid-19 di Kota Semarang. Kota Semarang sebagai ibukota Provinsi Jawa Tengah menjadi daerah paling tinggi penemuan kasus terpapar positif Covid-19.Pelaksana dalam kebijakan Pembatasan Kegiatan Masyarakat (PKM) adalah Gugus Tugas Covid-19 Kota Semarang. Adapun Pembatasan Kegiatan Masyarakat meliputi 4 pembatasan yaitu penghentian pelaksanaan kegiatan di sekolahan dan/atau institusi pendidikan, pambatasan kegiatan di tempat kerja, pembatasan kegiatan keagamaan, dan pembatasan di tempat umum. Penelitian ini bertujuan untuk mendeskripsikan proses implementasi Kebijakan Pembatasan Kegiatan Masyarakat (PKM) yang dilakukan oleh Pemerintah Kota Semarang dan untuk mendeskripsikan faktor-faktor pendukung dan penghambat mplementasi kebijakan. Penelitian ini merupakan penelitian kualitatif deskriptif.Pengumpulan data dilakukan dengan observasi, studi dokumen, wawancara dan online. Teknik analisis data meliputi reduksi data, penyusunan data dan kesimpulan .Uji validitas data menggunakan triangulasi sumber dan teknik. Hasil Penelitian ini yaitu implementasi kebijakan Pembatasan Kegiatan Masyarakat (PKM) di Kota Semarang menunjukkan Implementasi PKM melalui Perwal, PKM dikomunikasikan dari Dinas Keshatan dan Gugus Tugas Covid-19,sumber daya fasilitas sudah mendukung seprti Rumah sakit, tempat isolasi , Medis, fasilitas protokol kesehatan, psikolog dan bantuan sembako, Disposisi pemerintah Kota Semarang melalui Gugus Tugas Covid-19 dan Dinas Kesehatan Kota Semarang telah memperlihatkan komitmen yang dimiliki dalam menjalankan kebijakan Pembatasan Kegiatan Masyarakat (PKM) sudah baik namun perubahan yang dicapai belum maksimal, struktur birokrasi dan SOP yang jelas tercantum dalam Keputusan Walikota Semarang Nomor 180/278 Tahun. Faktor yang mendukung: komunikasi, dukungan, sumber daya, dan struktur birokrasi. Faktor yang menghambat: disposisi pemerintah yang komitmen namun masyarakat yang cendrung melanggar aturan Pembatasan Kegiatan Masyarakat (PKM). Kata Kunci: Implementasi, Kebijakan, Pembatasan Kegiatan Masyarakat (PKM), Kota Semarang.